2007
DOI: 10.1111/j.1365-2559.2007.02732.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of c‐Met, its ligand HGF/SF and HER2/neu in DCIS and adjacent normal breast tissue

Abstract: An imbalance in c-Met expression between tumour and surrounding normal tissue is associated with an aggressive DCIS phenotype. Moreover, c-Met and HGF/SF may contribute to tumour development by different means than those controlled by Her2/neu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
(109 reference statements)
0
40
0
Order By: Relevance
“…Increased cell proliferation, survival, motility, and extracellular matrix degradation resulting from the pathway activation contributes to tumor growth, invasiveness, and metastasis (Parr et al, 2004). In fact, high levels of HGF and Met expression associated with invasive human breast cancer have been considered as possible indicators of earlier recurrence and shortened survival in these patients (Lindemann et al, 2007). On the contrary, HGF expression but not Met is strongly suppressed in normal breast epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased cell proliferation, survival, motility, and extracellular matrix degradation resulting from the pathway activation contributes to tumor growth, invasiveness, and metastasis (Parr et al, 2004). In fact, high levels of HGF and Met expression associated with invasive human breast cancer have been considered as possible indicators of earlier recurrence and shortened survival in these patients (Lindemann et al, 2007). On the contrary, HGF expression but not Met is strongly suppressed in normal breast epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, HGF expression but not Met is strongly suppressed in normal breast epithelial cells. HGF and Met are therefore candidate targets for therapeutic intervention for the treatment of breast cancer (Lindemann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…5 A and B). Tumor cores were evaluated similar to Lindemann et al (25): 0, no immunoreactivity; 1, weak immunoreactivity; 2, moderately strong immunoreactivity; 3, strong immunoreactivity. Immunohistochemistry for ER, PR, ERBB2, EGF receptor (EGFR), and CK5/6 also was performed, and subtypes were determined as described (21,26).…”
Section: Met Expression Is Enhanced In Basal Andmentioning
confidence: 99%
“…While in the early years after its discovery Met was thought to be downregulated or absent in breast cancer, later studies showed a clear presence of the receptor in malignant breast tissue [146][147][148]. High Met protein expression levels fluctuate in studies, varying from 22-72% [64,[149][150][151][152][153][154][155][156]. HGF is not largely studied in breast cancer, protein expression in the literature range from 46-66%, when not considering localisation [150,[155][156][157].…”
Section: Proteins Of Interest In Breast Cancer Tumoursmentioning
confidence: 99%
“…Met and EGFR are reported to be involved in aggressive disease [138,153,156,[158][159][160]. An aggressive disease is indicated if the tumour is ER-negative, HER2-positive or triple-negative, and highly proliferative (as measured by NHG or S-phase fraction).…”
Section: Genes and Proteins In Relation To Clinicopathological Characmentioning
confidence: 99%